PENERAPAN FIQIH MUAMALAH PADA EKONOMI ISLAM MELALUI DANA CSR UNTUK KEADILAN SOSIAL - Nawal Riska Salsabila; Nurah Andini Rahmani Rizki; Hilmi Ahsan Sutisno; Muhammad Ridlo Assyauqi (Media Riset Bisnis Manajemen Akuntansi, 2025)
This research examines the application of fiqh muamalah in Islamic economic practice by utilizing Corporate Social Responsibility (CSR) funds as a solution to overcome social inequality. This research uses a qualitative approach with a library research method. The main focus of this approach is to understand in depth how the principles of fiqh muamalah are applied in Islamic economic practice, especially in the management of Corporate Social Responsibility (CSR) funds as an effort to realize social justice. This approach was chosen because it is in accordance with the purpose of the study, which emphasizes conceptual and interpretative understanding of literary data. Thus, CSR functions as a manifestation of corporate social responsibility, as well as a means of da'wah bil hal that spreads benefits widely and reflects the principle of rahmatan lil 'alamin. This application is also in line with DSN-MUI fatwa No. 77/DSN-MUI/VII/2010, which emphasizes the importance of CSR management according to sharia principles. Fatwa DSN-MUI No. 77/DSN-MUI/VII/2010 provides guidance on the implementation of CSR in accordance with sharia, including the management of halal funds, setting clear social goals, and applying the principles of transparency and sustainability. In conclusion, CSR in the view of fiqh muamalah is a very important strategy to create a fair, sustainable and inclusive Islamic economic order. This is particularly relevant in Indonesia, which is a Muslim-majority country.Keywords : fiqih muamalah, ekonomi islam, corporate social responsibility, keadilan sosial